Pengaruh Game Online Terhadap Gangguan Depresif Pada Mahasiswa Esco Surabaya - Arief Ibrahim, Caraka; Hapsery, Alfisyahrina (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2025)
Online games are one of the most popular games nowadays. The negative impacts that may arise from playing online games are mental health disorders such as higher emotional distress, anxiety, depression, and antisocial behavior. The results of the SEM-PLS analysis show that the research model for activity factors in playing online games that influence depressive disorders in students in Surabaya has an R2 value of 56.7%, which is a good enough model to explain the influence of existing variables. Hypothesis testing shows that the latent variables of the influence of achievement and the influence of activity significantly influence the increase in the level of depressive symptoms of students in Surabaya with parameter values of 0.335 and 0.561, which proves that depressive symptoms can be influenced by activity factors in playing online games